Child portraits by Daniel Pajuelo for TAFOS El Agustino (1986-1988) - Leiva Vizconde, Juan Carlos Manuel (2022)
Daniel Pajuelo was a member of Social Photography Workshop (TAFOS) in El Agustino by Thomas Müller and El Agustino’s Educative Services (SEA). The sample under analysis consists of two photographs from the TAFOS-PUCP archive, which explore the condition of the infants of the district between 1986 and 1988. Through the analysis we try to find out how these children were represented in Pajuelo’s photos. Those kids were emphasized with soft textures and contrast with the materials from the urban áreas of El Agustino.